Drynaether A, a new flavan from the drynaria bonii rhizomes - Pham, Thi Nhat Trinh; Mai, Dinh Tri; Dang, Chi Hien; Nguyen, Huu An; Phan , Nhat Minh; Pham, Ngoc An; Le, Tien Dung (Journal of Technical Education Science, 2016)
In Vietnam, the medicinal plant Drynaria bonii H. Christ is used for the treatment of osteoporosis, bone fractures, to stimulate the growth of hair and to treat tinnitus. In this paper, experiments were designed to investigate the proliferation activity of ethanol, n-hexane, chloroform, ethyl acetate and methanol extracts from D. bonii rhizomes on MG-63 human osteoblast-like cells. The results showed that methanol and hexane extracts had the ability to proliferate MG-63 cells at the concentration varying from 0.1 to 0.01µg/ml. In particular, at the concentration of 0.01µg/ml, hexane and methanol extracts illustrated the highest proliferation ratio with percentage of 9.31% and 6.16%, respectively. By column chromatography, a new compound named drynaether A (1) and five known compounds including uracil (2), 4’-hydroxy-7-methoxyflavan (3), kaempferol (4), indole-3-carboxylic acid (5) and protocatechuic acid (6) were isolated and identified from the methanol extract.